2022
DOI: 10.3389/fimmu.2022.1057421
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to white spot syndrome virus in the European shore crab is associated with suppressed virion trafficking and heightened immune responses

Abstract: IntroductionAll decapod crustaceans are considered potentially susceptible to White Spot Syndrome Virus (WSSV) infection, but the degree of White Spot Disease (WSD) susceptibility varies widely between species. The European shore crab Carcinus maenas can be infected with the virus for long periods of time without signs of disease. Given the high mortality rate of susceptible species, the differential susceptibility of these resistant hosts offers an opportunity to investigate mechanisms of disease resistance.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…WSSV's reported host range currently includes seventy-three species of shrimps, crabs, lobsters, freshwater shrimp and crayfish, brine shrimp, copepods, and polychaetes [93,152,[185][186][187][188][189][190][191][192][193][194][195][196][197][198][199], but the degree of species susceptibility to WSSV varies widely [200]. Penaeid shrimp species are highly susceptible and WSSV infection often results in high mortality.…”
Section: Species-susceptibilitymentioning
confidence: 99%
“…WSSV's reported host range currently includes seventy-three species of shrimps, crabs, lobsters, freshwater shrimp and crayfish, brine shrimp, copepods, and polychaetes [93,152,[185][186][187][188][189][190][191][192][193][194][195][196][197][198][199], but the degree of species susceptibility to WSSV varies widely [200]. Penaeid shrimp species are highly susceptible and WSSV infection often results in high mortality.…”
Section: Species-susceptibilitymentioning
confidence: 99%
“…Phagocytosis is regarded as a requisite part of innate immunity, which is initiated by recognizing the target particle and binding it to the phagocyte, then the immunerelated genes such as dynamin involved in the control of endocytosis via clathrin-mediated endocytosis [26,[52][53][54]. It is reported that the phagocytic activity of Fenneropenaeus indicus was higher in seawater containing brown algae (Sargassum glaucescens) [55].…”
Section: Effects Of Macroalgaementioning
confidence: 99%